Sonidegib en el tratamiento del carcinoma basocelular localmente avanzado (2020)
Sonidegib is an antagonist of the transmembrane protein Smoothened in the Hedgehog signaling pathway. It is indicated for the treatment of locally advanced basal cell carcinoma (BCC) that is not amenable to curative surgery or radiotherapy. Sonidegib’s efficacy and safety were demonstrated in the phase 2 BOLT trial, where 61% (95% CI, 48%–72%) of patients with locally advanced BCC treated with sonidegib 200 mg achieved an objective response to treatment with a mean time to response of 4 months. The median duration of response was 26.1 months and the median progression-free survival was 22.1 months. The most common adverse events were muscle spasms (54.4%), hair loss (49.4%), and loss of taste (44.3%); most events were grade 1 or 2. In this review, we summarize the main findings on the efficacy, safety, and tolerability of sonidegib and discuss the management of locally advanced BCC with this drug.